2017
DOI: 10.1056/nejmoa1614814
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Mutations in Endometriosis without Cancer

Abstract: BACKGROUND Endometriosis, defined as the presence of ectopic endometrial stroma and epithelium, affects approximately 10% of reproductive-age women and can cause pelvic pain and infertility. Endometriotic lesions are considered to be benign inflammatory lesions but have cancerlike features such as local invasion and resistance to apoptosis. METHODS We analyzed deeply infiltrating endometriotic lesions from 27 patients by means of exomewide sequencing (24 patients) or cancer-driver targeted sequencing (3 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
479
4
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(544 citation statements)
references
References 48 publications
(48 reference statements)
42
479
4
19
Order By: Relevance
“…Although further research is required for validation, one plausible explanation for this is that ectopic lesions may be derived from two cellular origins, namely initial establishment of the epithelial compartment by endometrial progenitor cells harboring cancer driver mutation, followed by stromal compartment establishment by BMDCs [194]. …”
Section: Cell-based Therapy For Endometriosis Treatmentmentioning
confidence: 99%
“…Although further research is required for validation, one plausible explanation for this is that ectopic lesions may be derived from two cellular origins, namely initial establishment of the epithelial compartment by endometrial progenitor cells harboring cancer driver mutation, followed by stromal compartment establishment by BMDCs [194]. …”
Section: Cell-based Therapy For Endometriosis Treatmentmentioning
confidence: 99%
“…Short PPS in CCC could have led to shorter OS in CCC cases, especially in EM-group patients. Although genetic difference in the tissue specimens was not evaluated in the present study, a report suggested that some patients carried driver mutations in ARID1A, PIK3CA, KRAS genes in benign deep infiltrating endometriosis (19). It is speculated that tumor samples of EM-group had potentially aggressive phenotype compared with non-EM group tumors.…”
Section: Discussionmentioning
confidence: 76%
“…Primary therapy using anti-cancer agents might alter genetic profile in CCC tumors, and cause refractory phenotype after recurrence. A report suggested CCC patients with Met gene amplification showed chemoresistant phenotype and worse prognosis (19). Thus, the alteration of genetic profiles affected by primary therapy might influence PPS in the patients with CCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact cause of endometriosis remains unknown, many theories have been presented, including retrograde menstruation (implantation) and stem cell theories . Endometriosis includes three subtypes: superficial peritoneal endometriosis, ovarian endometriosis, and deep infiltrating endometriosis (DIE), although there is a large degree of overlap between these three categories, and they are not well defined. DIE is a highly invasive form of endometriosis that is often characterised by nodules with painful symptoms .…”
Section: Kras Mutation In Endometriosis Lesions Of 19 Patientsmentioning
confidence: 99%